Augmented Reality Application-Based Teaching Material's Effect on Viscera Learning Through Algorithmic Thinking - Ebru Turan Güntepe; Necla Dönmez Usta (Journal of Science Learning, 2021)
The study aimed to examine AR-based teaching material's effect on viscera learning through algorithmic thinking by the primary school teacher candidates who are sophomores in the classroom teaching department in the spring term of the 2018-2019 academic year at a state university in the Eastern Black Sea and selected by convenience method. Viscera Information Form (VIF) and Application Process and AR Survey Form (APSF) were used as data collection tools in the study. VIF included subjects viscera in a human model and placed them in the skeletal structure. The other form, APSF, is about the application process and the material prepared with augmented reality. While the data obtained from VIF were analyzed under the researcher-defined categories regarding the participants' showing each viscera in a human torso model and placing them in the skeletal structure, the data obtained from APSF was processed with content analysis. The study results revealed that AR-based teaching material makes a positive contribution to the learning of viscera through algorithmic thinking. In addition, this is determined as AR-based teaching material contributes to understanding the related basic concepts through algorithmic thinking.